A qualitative study of patients' experience of living with inflammatory bowel disease: A preliminary focus on the notion of adaptation. (November 2016) - Matini, Lawrence; Ogden, Jane
This study investigates the lived experience of inflammatory bowel disease with the aim of examining the process of adapting to life with inflammatory bowel disease. Adaptation is often referred to as the desirable outcome in chronic illnesses such as inflammatory bowel disease; yet little is known as to how this is achieved. A total of 10 Crohn's and 12 ulcerative colitis patients recruited from online support networks participated in individual, semi-structured interviews. The study has identified the notion of a 'new normal' as central to adaptation, whereby patients seek to recover a sense of normality by finding an equilibrium between their lives before and after diagnosis.